Low-melting-point sealing glass powder
By increasing zinc borate in low-melting point sealing glass powder and reducing the content of active boron trioxide, the problem of strength reduction and reliability of traditional low-melting point glass powder under high temperature and high humidity conditions is solved, and higher sealing strength and reliability are achieved.
Patent Information
- Application Number
- CN202411862171.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-03-28
AI Technical Summary
The active boron trioxide in traditional low-melting glass powder dissolves under high temperature and high humidity conditions, resulting in reduced strength and reliability problems of sealing parts.
Low-melting point sealing glass powder containing 10-60% zinc borate is used to adjust the raw material components and process flow to reduce the content of active boron trioxide in the glass powder and improve the strength and reliability of the sealing parts.
It effectively reduces the content of active boron trioxide in the glass powder, improves the strength and reliability of the sealing parts, and avoids the strength reduction and reliability problems caused by the dissolution of active boron trioxide.
Smart Images

Figure CN119707291A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to sealing glass powder, in particular to a low melting point sealing glass powder. Background Art
[0002] Low-temperature sealing glass refers to the intermediate layer of glass that seals glass, ceramics, metals and composite materials together, mainly referring to sealing glass with a melting point significantly lower than that of ordinary glass. With the development of modern science and technology, especially the rapid progress in vacuum electronics, microelectronics, laser and infrared technology, electric light sources, high-energy physics, aerospace industry, energy, automobile industry, chemical industry, industrial testing and other fields, the miniaturization of devices and the precision of structural elements are constantly improving, the types of electronic components are increasing, and the shapes of products are becoming more and more complex. They have higher and higher requirements for the airtightness and reliability of sealed products, and the requirements for the working environment are also increasing. As a kind of sealing material, glass powder has a wide range of applications because it is superior to organic polymer materials in terms of UV resistance, heat resistance and weather resistance, and superior to metal materials in terms of electrical insulation performance.
[0003] The sealing temperature of the sealing glass powder is the key process parameter and indicator for this type of material. The reduction of the sealing temperature is conducive to simplifying the electronic device manufacturing process. Low-temperature sealing can prevent the deformation and oxidation of metal parts. If the melting point of the sealing glass powder is too high, it will be detrimental to the fluidity of the glass melt during sealing, so that the glass body cannot cover the entire sealing space, thus affecting the airtightness of the sealing part.
[0004] Traditional low-melting-point glass powder often contains ingredients such as boron trioxide. Although most of the boron trioxide will be dissolved in the glass powder to form water-insoluble compounds during the high-temperature melting process, due to various reasons, the boron trioxide cannot be completely dissolved in the glass powder to form water-insoluble compounds. This part of the boron trioxide can be dissolved in water or alcohol and other solutions, which is the active boron trioxide in the glass powder. The active boron trioxide in the glass seal is dissolved in the adsorbed water under high temperature and high humidity conditions, which significantly reduces the strength of the seal and even causes desoldering, seriously affecting the reliability of the glass welded parts. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a low-melting-point sealing glass powder with good reliability.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is a low melting point sealing glass powder, The raw material components are achieved by the following proportions by mass percentage: The components of the raw materials include bismuth oxide: 50-70%; zinc oxide: 1-5%; zinc borate: 10-30%; spodumene: 5-10%; and quartz: 2-5%.
[0007] The chemical components of the low-melting-point sealing glass powder described above include, by mass percentage, Bi2O3: 62-68%; B2O3: 10-12%; ZnO: 10-12%; SiO2: 9-11%; Al2O3: 0.5-11.5%; Li2O: 0.2-1%; and CaO: 1-2%.
[0008] The low-melting-point sealing glass powder described above, the preparation method of the low-melting-point sealing glass powder comprises the following steps: 1) Mix and dry the raw materials; 2) Mix by ball milling; 3) Melt the powder into glass at a high temperature of 800-1300℃ in a frit furnace; 4) Cool and crush the glass; 5) Dry and grind the crushed glass sand into powder.
[0009] The low-melting-point sealing glass powder of the invention adopts 10-60% of zinc borate as a raw material, which can reduce the content of active boron trioxide in the glass powder, and the sealing part has high strength and good reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0011] Figure 1 The invention discloses a low melting point sealing glass powder welding LED ultraviolet light window. Cross-sectional structural diagram. DETAILED DESCRIPTION
[0012] The low melting point sealing glass powder in the embodiment of the present invention is borosilicate glass powder or bismuth glass powder.
[0013] 1. Borosilicate glass powder, chemical composition range (mass percentage), R2O (alkali metal oxide): 3-10%; RO (alkaline earth metal oxide): 3-30%; B2O3: 10-30%; Al2O3: 0-20%; SiO2: 30-70%; other metal oxides 0-10%.
[0014] Raw material composition range: potassium feldspar powder: 20-60%; spodumene powder: 0-30%; lithium carbonate: 0-5%; boric acid: 0-40%; zinc borate: 10-60%; lithium borate: 0-10%; zinc oxide: 0-20%; calcium carbonate: 0-20%; quartz powder: 0-50%; kaolin: 0-30%, other metal oxides: 0-10%.
[0015] 2. Bismuth glass powder, chemical composition range (mass percentage), Bi2O3: 50 ~ 90%; B2O3: 2 ~ 12%; SiO2: 0 ~ 20%; ZnO: 0 ~ 20%; other metal oxides 0 ~ 10%.
[0016] Raw material composition range: bismuth oxide: 50-90%; boric acid: 0-20%; zinc borate: 10-30%; bismuth borate: 0-50%; zinc oxide: 0-100%; calcium carbonate: 0-10%; quartz powder: 0-30%; kaolin: 0-20%, other metal oxides: 0-10%.
[0017] The raw materials involved in the embodiments of the present invention are as follows: potassium feldspar (K2O content is greater than 12%); calcium carbonate (industrial pure or analytical pure); lithium carbonate (industrial pure or analytical pure); spodumene (industrial pure or analytical pure); bismuth oxide (industrial pure or analytical pure); zinc oxide (industrial pure or analytical pure); boric acid (industrial pure or analytical pure); zinc borate (industrial pure or analytical pure); bismuth borate (industrial pure or analytical pure); lithium borate (industrial pure or analytical pure); quartz powder (industrial pure); kaolin (industrial pure); other metal oxides (industrial pure).
[0018] The equipment and main tools involved in the embodiments of the present invention include: electronic balance, jar mill, corundum jar, agate ball, oven, frit furnace, hammer crusher, dry pressing machine, air atmosphere tubular furnace, nitrogen atmosphere mesh belt furnace, digital display push-pull testing machine, and salt spray testing machine.
[0019] The process flow of preparing and testing the low-melting-point sealing glass powder of the present invention is as follows: 1. mixing and drying the raw materials; 2. ball milling and mixing; 3. melting the powder in a frit furnace at high temperature to form glass (800-1300°C); 4. rapid cooling and crushing of the glass body; 5. drying the glass sand and ball milling it into powder; 6. granulation by screening the glass powder; 7. dry pressing to form a solder ring; 8. high-temperature sintering and hardening (aging) of the solder ring; 9. assembling the shell, glass and solder ring into a light window and welding them in a mesh furnace at high temperature; 10. strength test, boiling water test and salt spray test, etc.
[0020] The chemical composition ratio of the bismuthate glass powder of comparative example 1 LT460-1 and example LT460-2 is the same. The chemical composition mass percentage is as follows: Bi2O3: 65%; B2O3: 11%; ZnO: 11%; SiO2: 10%; Al2O3: 1%; Li2O: 0.5%; CaO: 1.5%.
[0021] Comparative Example 1 The raw material composition of bismuthate glass powder LT460-1 is: Bismuth oxide powder: 59.5%; Boric acid: 18%; Zinc oxide powder: 10%; Spodumene powder: 7%; Calcium carbonate powder: 2%; Quartz powder: 3.5%.
[0022] Example 1 The raw material composition of bismuthate glass powder LT460-2 is: Bismuth oxide powder: 62.5%; Zinc oxide: 2%; Zinc borate powder: 22.5%; Spodumene powder: 7.4%; Calcium carbonate powder: 2%; Quartz powder: 3.6%.
[0023] The process flow is as follows: 1. Mix and dry the raw materials; 2. Mix by ball milling; 3. Melt the powder into glass (1100℃) at high temperature in a furnace; 4. Rapidly cool and break the glass body; 5. Dry and ball grind the glass sand into powder; 6. Granulate the glass powder by screening; 7. Dry press to form a solder ring; 8. Sinter and harden (age) the solder ring at high temperature; 9. Assemble the shell, glass and solder ring into a light window and weld them in a furnace at high temperature; 10. Strength test, boiling water test and salt spray test. In comparative example 1, the boron trioxide in the bismuth glass powder (LT460-1) is added with boric acid, ball-milled into powder, and then melted in a frit furnace at 1100°C for two hours; in example 1, the boron trioxide in the bismuth glass powder (LT460-2) is calculated, added with zinc borate or bismuth borate, ball-milled into powder, and then melted in a frit furnace at 1100°C for two hours.
[0024] After LT460-1 and LT460-2 are melted, they are crushed and ball-milled into powders. 10.000g of each is taken and baked at 160℃ for 5h, 300g of pure water is added and boiled for 1h, the precipitation is filtered, and then 200g of cold water is added, stirred, precipitated and filtered, and placed in an oven and baked at 160℃ for 5h, and the weight loss is obtained by weighing.
[0025] The weight loss of LT460-1 in comparative example 1 was 1.72%, and the weight loss of LT460-2 in example 1 was 0.65%. The water-soluble substances in LT460-2 were significantly less than those in LT460-1.
[0026] Solder rings are made by dry pressing LT460-1 and LT460-2 glass powders. Solder ring 10 is as follows: Figure 1 The outer diameter D is 3.5mm, the inner diameter d is 2.2mm, and the height h is 0.7mm, which is used to weld LED ultraviolet light windows. For example, when welding a 4J29 Kovar housing 20 and a sapphire glass sheet 30, after initial testing after welding, the average vertical thrust value from bottom to top of the sapphire glass sheet 30 for LT460-1 is 53N, and the average vertical thrust value from bottom to top of the sapphire glass sheet 30 for LT460-2 is 52N. Then, the welded parts are boiled in water for 30 minutes, and then immediately subjected to strength testing. The average vertical thrust value from bottom to top of the sapphire glass sheet 30 for LT460-1 is 18N, and the average vertical thrust value from bottom to top of the sapphire glass sheet 30 for LT460-2 is 31N. After the 72h salt spray test, the strength test was immediately carried out. The average vertical thrust value from bottom to top on the sapphire glass sheet 30 of LT460-1 was 17N, and the average vertical thrust value from bottom to top on the sapphire glass sheet 30 of LT460-2 was 27N.
[0027] Example 2 and Comparative Example 2: The chemical composition ratio of the borosilicate glass powder ZT750-1 of comparative example 2 and the borosilicate glass powder ZT750-2 of example 2 is the same, and the chemical composition by mass percentage is: K2O+Na2O: 9%; B2O3: 21%; ZnO: 20%; Al2O3: 12%; SiO2: 38%.
[0028] In terms of mass percentage, the raw material composition of borosilicate glass powder ZT750-1 in comparative example 2 is: Potassium feldspar powder: 50.5%; Boric acid: 32%; Zinc oxide powder: 17.5%.
[0029] In terms of mass percentage, the raw material composition of borosilicate glass powder ZT750-2 in Example 2 is as follows: Potassium feldspar powder: 55%; Zinc borate: 42%; Zinc oxide powder: 3%.
[0030] The process flow is as follows: 1. Mix and dry the raw materials; 2. Mix by ball milling; 3. Melt the powder into glass (1050℃) at high temperature in a furnace; 4. Rapidly cool and break the glass; 5. Dry and ball grind the glass sand into powder; 6. Granulate the glass powder by screening; 7. Dry press to form a solder ring; 8. Sinter and harden (age) the solder ring at high temperature; 9. Assemble the shell, glass and solder ring into a light window and weld them in a furnace at high temperature; 10. Strength test, boiling water test and salt spray test.
[0031] Comparative Example 2 Boric acid was added to the boron trioxide in ZT750-1, which was ball-milled into powder and then melted in a frit furnace at 1050°C for two hours. Example 2 Boron trioxide in ZT750-2 was calculated and added as zinc borate, which was ball-milled into powder and then melted in a frit furnace at 1050°C for two hours.
[0032] After ZT750-1 and ZT750-2 are melted, they are crushed and ball-milled into powder. 10.000g of them are taken and baked at 160℃ for 5h. 300g of pure water is added and boiled for 1h. The precipitation is filtered. Then 200g of cold water is added, stirred, precipitated and filtered. The mixture is placed in an oven and baked at 160℃ for 5h. The weight loss is obtained by weighing.
[0033] The weight loss of ZT750-1 is 1.13%, and the weight loss of ZT750-2 is 0.45%. The water-soluble matter of ZT750-2 is less than that of ZT750-1.
[0034] The solder rings were made by dry pressing ZT750-1 and ZT750-2 glass powders to weld LED UV light windows, i.e., welding 4J34 Kovar housing and sapphire glass sheets. The average vertical thrust from bottom to top of sapphire glass sheet 30 by ZT750-1 was 62N, and the average vertical thrust from bottom to top of sapphire glass sheet 30 by ZT750-2 was 60N. Then, these welded parts were boiled in water for 30 minutes and immediately subjected to strength tests. The average vertical thrust from bottom to top of sapphire glass sheet 30 by ZT750-1 was 48N, and the average vertical thrust from bottom to top of sapphire glass sheet 30 by ZT750-2 was 55N. After the 72h salt spray test, the strength test was immediately carried out. The average vertical thrust value from bottom to top on the sapphire glass sheet 30 of ZT750-1 was 43N, and the average vertical thrust value from bottom to top on the sapphire glass sheet 30 of ZT750-2 was 51N.
[0035] Example 3 and Comparative Example 3: Borosilicate glass powder Comparative Example 3 ZT700-1 and Example 3 ZT700-2 have the same chemical composition ratio. Chemical composition (mass percentage): K2O+Na2O: 8%; Li2O: 1%; B2O3: 21%; ZnO: 20%; Al2O3: 11%; SiO2: 39%; Borosilicate glass powder comparative example 3 ZT700-1 raw material composition is: Potassium feldspar powder: 38%; spodumene powder: 13%; boric acid: 32%; zinc oxide powder: 17%.
[0036] Borosilicate glass powder Example 3 ZT700-2 raw material composition is: Potassium feldspar powder: 41%; spodumene powder: 14%; zinc borate: 42%; zinc oxide powder: 3%.
[0037] Process flow: 1. Mix and dry the raw materials; 2. Mix by ball milling; 3. Melt the powder into glass (1000℃) at high temperature in a furnace; 4. Rapidly cool and break the glass; 5. Dry and ball grind the glass sand into powder; 6. Granulate the glass powder by screening; 7. Dry press to form solder ring; 8. Sinter and harden (age) the solder ring at high temperature; 9. Assemble the shell, glass and solder ring into a light window and weld them in a furnace at high temperature; 10. Strength test, boiling water test and salt spray test, etc.
[0038] In comparative example 3 ZT700-1, boron trioxide is added with boric acid, ball-milled into powder and then melted in a frit furnace at 1000°C for two hours; in example 3 ZT700-2, boron trioxide is added with zinc borate by calculation, ball-milled into powder and then melted in a frit furnace at 1000°C for two hours.
[0039] Comparative Example 3 ZT700-1 and Example 3 ZT700-2 were melted and crushed into powder. 10.000 g of the powder was baked at 160°C for 5 h, 300 g of pure water was added and boiled for 1 h, the precipitate was filtered, and 200 g of cold water was added and stirred to precipitate and filter. The powder was placed in an oven and baked at 160°C for 5 h, and the weight loss was obtained by weighing.
[0040] The weight loss of ZT700-1 in comparative example 3 was 1.08%, and the weight loss of ZT700-2 in example 3 was 0.39%. The water-soluble matter in ZT700-2 in example 3 was less than that in ZT700-1 in comparative example 3.
[0041] The glass powders of Comparative Example 3 ZT700-1 and Example 3 ZT700-2 were dry pressed to form solder rings, and the LED UV light window, i.e., the 4J33 Kovar shell and the sapphire glass sheet, were welded. The average vertical thrust from bottom to top of the sapphire glass sheet 30 of Comparative Example 3 ZT700-1 was 48 N, and the average vertical thrust from bottom to top of the sapphire glass sheet 30 of Example 3 ZT700-2 was 47 N. Then, the welded parts were boiled in water for 30 minutes, and the strength test was immediately carried out. The average vertical thrust from bottom to top of the sapphire glass sheet 30 of Comparative Example 3 ZT700-1 was 32 N, and the average vertical thrust from bottom to top of the sapphire glass sheet 30 of Example 3 ZT700-2 was 38 N. After the 72h salt spray test, the strength test was immediately performed. The average vertical thrust value from bottom to top on the sapphire glass sheet 30 of ZT700-1 in comparative example 3 was 31N, and the average vertical thrust value from bottom to top on the sapphire glass sheet 30 of ZT700-2 in embodiment 3 was 35N.
[0042] The low melting point sealing glass powder of the above embodiments of the present invention uses insoluble or slightly soluble borates, such as zinc borate or bismuth borate, instead of boric acid as a raw material, which can reduce the content of active boron trioxide in the glass powder, and the sealing component has high strength and good reliability.
Claims
1. A low melting point sealing glass powder, characterized in that: The raw material components are achieved by the following proportions by mass percentage: The components of the raw materials include bismuth oxide: 50-70%; zinc oxide: 1-5%; zinc borate: 10-30%; spodumene: 5-10%; and quartz: 2-5%.
2. The low melting point sealing glass powder according to claim 1, characterized in that: Its chemical components include Bi2O3: 62~68%; B2O3: 10~12%; ZnO: 10~12%; SiO2: 9~11%; Al2O3: 0.5~11.5%; Li2O: 0.2~1%; CaO: 1~2%.
3. The low-melting-point sealing glass powder according to any one of claims 1 to 2, characterized in that: The preparation method of the low-melting-point sealing glass powder comprises the following steps: 1) mixing and drying the raw materials; 2) ball milling and mixing; 3) melting the powder into glass at a high temperature of 800-1300° C. in a frit furnace; 4) rapidly cooling and crushing the glass body; 5) drying and ball milling the crushed glass sand into powder.